Group B Streptococci Induce Interleukin 8 Production in Human Cervical Epithelial Cell Cultures: The Role of Capsule Polysaccharide - AKSU, MEHMET BURAK (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objective: Group B streptococci (GBS) are the major cause of pneumonia, sepsis, and meningitis in neonates and adults. Epithelial invasion and early cytokine response of female genital tract considered to be important in the pathogenesis of GBS infection. In this study, we studied the IL-8 induction in cervical epithelial cells in response to stimulus with encapsulated (COH1) and unencapsulated (COH1-13) strains of group B streptococci. Methods: Human cervical epithelial cell (HeLa) cultures were stimulated with different concentrations (10(6) CFU/ml and 10(8) CFU/ml) of two GBS strains. E.coli LPS was used as positive control and at specified time points (4, 8 and 24 hour) cell culture supernatant samples were collected. IL-8 level in samples was quantified by using ELISA assay. Results: Both GBS strains caused an equal IL-8 response in HeLa cells in a time-dependent manner. In addition, cytokine levels triggered by different bacterial concentrations were similar and comparable with LPS. Conclusion: Our study showed that GBS induce proinflammatory IL-8 levels in cervix epithelial cells. This induction seems to be independent from capsule polysaccharides and suggesting that other bacterial components are involved in IL-8 stimulation.
Keywords: Streptococcus Group B; bacterial capsule; epithelial cells; IL-8; TUMOR-NECROSIS-FACTOR